I've been having some trouble solving this equation. (The solution in my book is given as $ \frac {n \pi}{3}, n \in Z $)

Here is what I've done

$$\frac {\sin \theta}{\cos \theta} + \frac {\sin 2\theta} {\cos 2\theta} + \frac{\sin 3\theta}{\cos 3\theta}= \frac {\sin \theta}{\cos \theta} \frac {\sin 2\theta} {\cos 2\theta} \frac{\sin 3\theta}{\cos 3\theta}$$

$$ \frac {\sin \theta \cos 2\theta \cos 3\theta + \cos \theta \sin 2\theta \cos 3\theta + \cos \theta \cos 2\theta \sin 3\theta - \sin \theta \sin 2\theta \sin 3\theta }{\cos\theta \cos 2\theta \cos 3\theta} = 0 $$

$$\cos 2\theta \{\sin\theta \cos 3\theta + cos \theta \sin 3\theta \} + \sin 2\theta \{\cos \theta \cos 3\theta - \sin \theta \sin 3\theta \} = 0 $$

$$\cos 2\theta \sin(3\theta + \theta) +\sin2\theta \cos(3\theta + \theta) = 0 $$

$$ \cos 2\theta \sin 4\theta + sin 2\theta cos 4\theta = 0$$

$$ \sin (2\theta + 4\theta) = 0$$

$$\sin 6\theta = 0 $$

$$ \theta = \frac {n\pi}{6}, n \in Z$$

I understand from this question that whatever mistake I am making is in the third step, where I remove $\cos \theta \cos 2\theta \cos 3\theta $ from the denominator. However, despite reading through the aforementioned post, I couldn't really get the intuition behind why this is wrong.

I'd like :

  1. To understand the intuition behind why removing $\cos \theta \cos 2\theta cos 3\theta $ is a mistake.
  2. To know how to solve this question correctly
  3. How do I avoid making these types of mistakes when solving trigonometric equations
  • 1
    $\begingroup$ The problem is that your expression is undefined if $\cos(\theta)$, $\cos(2\theta)$ or $\cos(3\theta)$ is $0$. $\endgroup$ – Robert Israel Feb 21 '17 at 7:07
  • $\begingroup$ The same question has been asked by @Siddhant. Check this out math.stackexchange.com/questions/1878004/… $\endgroup$ – Saksham Feb 21 '17 at 17:21

You could have solved the problem using the tangent multiple angle formulae.

Using $t=\tan(\theta)$ $$\tan(2\theta)=\frac{2t}{1-t^2}\qquad \tan(3\theta)=\frac{3t-t^3}{1-3t^2}$$ This makes, after some minor simplifications

$$\tan \theta + \tan 2\theta + \tan 3\theta - \tan \theta \tan 2\theta \tan 3\theta=\frac{2 t \left(3-t^2\right)}{1-t^2}=0$$ and then the solutions assuming that ${1-3t^2}\neq 0$ and ${1-t^2}\neq 0$.


your intuition should be correct here's why

$\left(\frac{\sin\theta}{\cos\theta}+\frac{\sin2\theta}{\cos2\theta }+\frac{\sin3\theta}{\cos3\theta}=\frac{\sin\theta\sin2\theta\sin3\theta}{\cos\theta\cos2\theta\cos3\theta}\right)*\cos\theta\cos2\theta\cos3\theta$

$\Rightarrow \sin\theta\cos2\theta\cos3\theta+\cos\theta\sin2\theta\cos3\theta+\cos\theta\cos2\theta\sin3\theta= \sin\theta\sin2\theta\sin3\theta$

$\Rightarrow \cos\theta(\sin2\theta\cos3\theta+\cos2\theta\sin3\theta )+\sin\theta(\cos2\theta\cos3\theta-\sin2\theta\sin3\theta)=0 $

$\Rightarrow \cos\theta\sin(2\theta+3\theta)+\sin\theta\cos(2\theta+3\theta)=0 $

$\Rightarrow sin([2\theta+3\theta]+\theta)=0 $

$\Rightarrow sin(6\theta)=0 $

So, I'm uncertain that your answer is wrong...


We have $$\tan (A+B+C) = \frac{\tan A + \tan B + \tan C - \tan A \tan B \tan C}{1-(\tan A \tan B + \tan B \tan C + \tan C \tan A)}$$ and the given condition implies that $\tan (6\theta) = 0$. Thus $\theta = \frac{n\pi}{6}$, $n \in \mathbb{Z}$


In your simplified expression there is $\cos 3 \theta $ term in the denominator that goes to zero for solution you obtained. Should be checked before accepting or discarding it as a valid solution.

I cannot resist an elementary trig approach ..

If $ (A+B+C) = 2 \pi, $ then $ {(\tan A + \tan B + \tan C) = \tan A \tan B \tan C} $

If $ {(\tan A + \tan B + \tan C) = \tan A \tan B \tan C} $ then $(A+B+C) = 2 \pi $

is among possible solutions.

In the above if $ A= t, B=2t, C=3t$ then $t= \pm 2 \pi/6= \pm \pi/3,\pm 2\pi/3, ... $

By inspection $ t= 0 ,\,2 k\pi,$ plus co-terminals


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.